Increased volumes of mildly elevated capillary transit time heterogeneity positively predict favorable outcome and negatively predict intracranial hemorrhage in acute ischemic stroke with large vessel occlusion - Potreck, Arne; Loebel, Sarah; Pfaff, Johannes; Østergaard, L.; Mouridsen, K.; Radbruch, A.; Bendszus, Martin; Mundiyanapurath, Sibu (European radiology, 2019)
ObjectivesIn patients with acute ischemic stroke, we aimed to investigate whether microvascular changes, as indexed by capillary transit time heterogeneity (CTH), contribute to the decline of the chance for favorable outcome over time and whether they are a predictor of an intracranial hemorrhage (ICH).MethodsWe retrospectively calculated CTH maps for 131 consecutive patients with acute ischemic stroke due to large vessel occlusion of the anterior circulation who had a relevant MRI PWI-DWI mismatch and were treated with endovascular thrombectomy (ET). Multivariable logistic regressions were conducted with favorable outcome (mRS ≤ 2 after 3 months) and occurrence of an ICH as dependent variables and the volume of mildly elevated CTH as independent variable adjusted for age, successful recanalization, hypertension, diabetes, atrial fibrillation, NIHSS score on admission, DWI lesion volume, and symptom-onset-to-treatment time (OTT).ResultsA larger volume of mildly elevated CTH was a positive predictor of favorable outcome (OR 1.17; 1.03-1.33; p = 0.019) and a negative predictor of ICH (OR 0.83; 0.73-0.96; p = 0.009). As expected, successful recanalization (OR 5.54; 1.8-17; p = 0.003), low NIHSS on admission (OR 0.9; 0.82-1.00; p = 0.045), short OTT (OR 0.96; 0.94-0.99; p = 0.006), and low DWI volume (OR 0.68; 0.49-0.94; p = 0.021) were also predictors of favorable outcome, whereas other negative predictors of ICH were atrial fibrillation (OR 2.69; 1.10-6.57; p = 0.030), high NIHSS score on admission (OR 1.10 (1.01-1.19); p = 0.030), and large DWI volume (OR 1.51; 1.17-1.19; p = 0.002).ConclusionAn increased volume of mildly elevated CTH is a positive predictor of favorable outcome and a negative predictor for ICH in patients with acute ischemic stroke and mismatch undergoing ET.Key Points • The classification of potentially salvageable tissue and infarct core based on traditional net perfusion parameters (as Tmax or CBF) does not account for the microvascular distribution of blood. • However, the microvascular distribution of blood, as indexed by the capillary transit time heterogeneity (CTH), directly affects the availability of oxygen within the hypoperfused tissue and should therefore be respected in acute ischemic stroke imaging. • In our study, mildly elevated CTH is found to be a positive predictor for a favorable clinical outcome and a negative predictor for the occurrence of an intracranial hemorrhage in patients with acute ischemic stroke and homogenous mismatch who underwent ET.
Gesehen am 06.12.2019